PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP PERKEMBANGAN ASET KEUANGAN SYARIAH DI INDONESIA - Budi Suharto; Muhamad Wardany Anwar (ITB AAS Indonesia Surakarta, 2026)
The Islamic financial system in Indonesia has demonstrated significant and strategic development, becoming a crucial pillar in supporting national economic stability and growth, with total assets reaching IDR 3,131.02 trillion by 2025. Although extensive research exists on the relationship between macroeconomic factors and the performance of Islamic banking, there remains a literature gap concerning the direct analysis of the influence of inflation and economic growth on the overall total assets of the Islamic financial sector (encompassing Islamic banking, capital markets, and non-bank financial institutions) during the post-pandemic period of 2021-2025. This study aims to fill this gap by providing the latest empirical evidence on how macroeconomic stability and economic growth shape the broader asset landscape of the Islamic financial industry. This research employs a quantitative approach using secondary time-series data for the period 2021-2025. The data utilized include statistics on the development of Islamic financial assets, annual inflation rates, and Indonesia's economic growth (Gross Domestic Product). The analysis identifies the relationships and influences of these macroeconomic variables on the development of Islamic financial assets. The findings indicate that Islamic financial assets in Indonesia experienced consistent and significant growth from 2021 to 2025. Indonesia's economic growth also showed a solid and stable recovery above 5% since 2022. Despite fluctuations in the inflation rate, the Islamic financial sector successfully maintained its growth momentum, demonstrating resilience amidst macroeconomic dynamics. Macroeconomic conditions, particularly inflation and economic growth, are crucial determinants in shaping the performance and development of the Islamic financial sector in Indonesia.